Kim and Omberg Revisited: The Duality Approach - Anna Battauz; Marzia De Donno; Alessandro Sbuelz (Journal of Probability and Statistics)
We give an alternative duality-based proof to the solution of the expected utility maximization problem analyzed by Kim and Omberg. In so doing, we also provide an example of incomplete-market optimal investment problem for which the duality approach is conducive to an explicit solution.